1999
DOI: 10.1002/cbm.313
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for non‐prescription of clozapine in treatment‐resistant schizophrenia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 12 publications
0
33
0
1
Order By: Relevance
“…This was replicated by Kelly et al , 18 who surveyed psychiatrists in Maryland, USA, and found that the main barrier, ranked highest on the Likert scale (1–5), was patient non-adherence with blood work (3.7 ± 1.1) and the burden of blood work on the patient (3.6 ± 1.2) 18 . In a survey of patients, Swinton and Ahmed (1999) 19 reported that almost two-thirds of participants did not want the burden of regular blood tests. This was replicated in a survey of staff, with 65% ( n = 83) reporting that patients did not want the burden of regular blood tests and that frequent blood tests were considered a major barrier to initiating clozapine 17 …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This was replicated by Kelly et al , 18 who surveyed psychiatrists in Maryland, USA, and found that the main barrier, ranked highest on the Likert scale (1–5), was patient non-adherence with blood work (3.7 ± 1.1) and the burden of blood work on the patient (3.6 ± 1.2) 18 . In a survey of patients, Swinton and Ahmed (1999) 19 reported that almost two-thirds of participants did not want the burden of regular blood tests. This was replicated in a survey of staff, with 65% ( n = 83) reporting that patients did not want the burden of regular blood tests and that frequent blood tests were considered a major barrier to initiating clozapine 17 …”
Section: Resultsmentioning
confidence: 89%
“…However, Nielson et al (2009) found that only 44.9% ( n = 44) would go to clozapine after two antipsychotics, 13 and about a third 30.6% ( n = 30) 13 of clinicians in one survey and 14% ( n = 19) in another would wait until three adequate trials of antipsychotics prior to initiating clozapine, while 18.4% ( n = 19) 13 would wait until more than three failed adequate trials of antipsychotics. In another survey, 28% ( n = 51, total 184) of consultants said they would trial at least another antipsychotic before going to clozapine after a failed trial of two antipsychotics, 22 and 40.5% ( n = 92) preferred to use several other antipsychotics before clozapine 19 . Nielson et al 13 found that 64.7% of psychiatrists surveyed ( n = 64) would rather combine two antipsychotics than prescribe clozapine, and 15.2% ( n = 15) would augment with a mood stabiliser before using clozapine in a non-schizoaffective state 13 …”
Section: Resultsmentioning
confidence: 99%
“…Various explanations have been suggested , but few studies have asked practitioners who are involved in prescribing decisions directly about their reasons for non‐prescribing of clozapine. Unfamiliarity with the guidelines had been suggested as an obvious reason for non‐adherence , but here we have found that the majority of practitioners report familiarity with the guidelines, indicating this does not explain non‐adherence among practitioners in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…Potential non‐compliance with oral therapy was also a concern which was identified in our study. Fears of non‐compliance have been identified previously as a barrier to prescribing , although compliance with clozapine is actually better compared with other antipsychotics . Recent data show that rehospitalisation rates for patients receiving depot medication are higher than those receiving clozapine , suggesting that the alternatives which guarantee compliance may still be worse for patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Auch hier ist aber ein direkter Effekt nicht mit Sicherheit nachgewiesen. Darüber hinaus ergibt sich, wie bei allen peroral verabreichten Medikamenten, bei vielen Zielgruppen das Problem der mangelnden Einnahmezuverlässigkeit, was dadurch belegt wird, dass in englischen High Security Hospitals der Hauptgrund für die Nichtverschreibung von Clozapin mangelnde Compliance war [150]. 2.…”
Section: Introductionunclassified